Penghayatan dan kesedaran partriotisme dalam kalangan pelatih Program Latihan Khidmat Negara - Razak, Mohd Hairul Anuar; Jawan, Jayum; Abd. Halim, Adlina; Ismail, Mohd Mahadee; Misri, Siti Aishah (Institut Penyelidikan Pembangunan Belia Malaysia, 2013)
The main objective of this study was to assess level of knowledge, perception and understanding among youth in the context of awareness and national spirit of patriotism. Data were collected using questionnaires with 1010 respondents from all state in Malaysia. Generally, findings indicated that majority of the respondents had high level of knowledge (83.5%), perception (98.7%) and understanding (83.1%) of patriotism. Findings also showed that the difference in races among Malay, Chinese, Indian and native of Sabah and Sarawak influence on the varied perception of patriotism and nationalism. Study also found that there was no significant difference between gender and the spirit of patriotism.